2005
DOI: 10.1292/jvms.67.563
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profile and Serosurvey for Virus Infections of Japanese Wild Boars in Shikoku Island

Abstract: ABSTRACT. To estimate the genetic background of Japanese wild boars inhibiting the 4 prefectures of Shikoku Island (Kagawa, Tokushima, Kouchi and Ehime), we examined haplotypes of mitochondrial DNA (mtDNA) and genotypes of the nuclear glucosephosphate isomerase-processed pseudogene (GPIP) in 189 wild boars. Of the 8 different mtDNA haplotypes (J5, J10, J12, J13, J15, J19, J20 and E33) detected in Shikoku Island, the first to be identified were J19 and J20 (of Japanese wild boar lineage) and E33 (of European do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 11 publications
(23 reference statements)
1
32
0
Order By: Relevance
“…When the 77 mtDNA haplotypes were compared with previously reported mtDNA sequences, the haplotype of sample No. 2007E45, isolated from Lombok Island, was identical to the haplotype M33 from domestic pig (Ishiguro and Nishimura 2005).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…When the 77 mtDNA haplotypes were compared with previously reported mtDNA sequences, the haplotype of sample No. 2007E45, isolated from Lombok Island, was identical to the haplotype M33 from domestic pig (Ishiguro and Nishimura 2005).…”
Section: Resultsmentioning
confidence: 87%
“…Neighbor-joining (NJ) phylogenetic tree constructed using the 572-bp to 574-bp mtDNA control region. This tree includes 76 novel mtDNA haplotypes from Indonesia identified in this study and 81 previously reported haplotypes (Hongo et al 2002;Ishiguro and Nishimura 2005;Ishiguro et al 2008a). Indonesian mtDNA haplotypes are the same as listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the reported seroprevalences of PRV in wild boars in western (10%) and eastern (9%) Germany [10,12], France (6%) [1], south-central Spain (56%) [5], Croatia (55%) [16] and the southern U.S.A. (34-61%) [2,6,7,14] seem to be higher than that in Japan (3%). In addition, only one previous report indicated that wild boars in Shikoku, in southern Japan, were free from PRV [8]. These results suggest that the low seroprevalence of PRV in wild boars in Japan might be indicative of the success of the PRV eradication program in domestic pigs.…”
mentioning
confidence: 80%